The departures of the Sacred Original of the Virgin of Guadalupe from the vicinity of Tepeyac - González Martín del Campo, Daniel (Metafísica y Persona, 2025)
This article provides a historical account of the times when the image of Santa María de Guadalupe had to be removed from the vicinity of Tepeyac. In the context of the second removal of the Sacred Original, it narrates the creation of the image that replaced the Ayate of San Juan Diego on the main altar of the Colegiata between 1926 and 1929, as well as the final fate of this "Twin".